New Curculionoidea records from New Brunswick, Canada with an addition to the fauna of Nova Scotia - Webster, Reginald P. (Zookeys, 2016)
Abstract. This paper presents 27 new records of Curculionoidea for the province of New Brunswick, Canada, including three species new to Canada, and 12 adventive species, as follows: Eusphryrus walshii LeConte, Choragus harrisii LeConte (newly recorded for Canada), Choragus zimmermanni LeConte (newly recorded for Canada) (Anthribidae); Cimberis pallipennis (Blatchley) (Nemonychidae); Nanophyes marmoratus marmoratus (Goeze) (Brentidae); Procas lecontei Bedel (Brachyceridae); Anthonomus pusillus LeConte (newly recorded for Canada), Anthonomus (Cnemocyllus) pictus Blatchley, Archarius salicivorus (Paykull), Dorytomus hirtus LeConte, Ellescus bipunctatus (Linnaeus), Mecinus janthinus (Germar), Myrmex chevrolatii (Horn), Madarellus undulatus (Say), Microplontus campestris (Gyllenhal), Pelenomus waltoni (Boheman), Rhinoncus bruchoides (Herbst), Rhinoncus perpendicularis (Reich), Cossonus impressifrons Boheman, Cossonus pacificus Van Dyke, Rhyncolus knowltoni (Thatcher), Eubulus bisignatus (Say), Polydrusus cervinus (Linnaeus), Magdalis piceae Buchanan, Procryphalus mucronatus (LeConte), Ips grandicollis (Eichhoff), and Xyleborinus attenuatus (Blandford). Recent name changes in the genus Rhinoncus are applied to species known from New Brunswick. In addition, Orchestes alni (Linnaeus) is newly recorded from Nova Scotia.